Eficiência e demanda nutricional de cultivares de melão em função de doses de fósforo - Sousa, Valdívia de Fátima Lima de (Universidade Federal Rural do Semi-Árido, 2018)
The melon crop presents a high demand for nutrients, with phosphorus (P) most limiting production. Due to the great majority of Brazilian soils present high P retention capacity, it is necessary to apply high doses of phosphates. Thus, we have intensified the search for the utilization of the adaptive potential of genotypes and the adverse conditions of soil fertility, seeking cultivars that present higher nutritional efficiency. In order to evaluate the efficiency and nutritional demand for phosphorus use in melon cultivars at different doses of phosphorus, two experiments were carried out from October to December 2015 (Experiment 1) and from August to November 2016 (Experiment 2). In both experiments the experimental design was completely randomized blocks and the treatments were distributed in subdivided plots with five replicates. In the plots were arranged the three doses of phosphorus (0, 105 and 210 kg ha-1, respectively, corresponding to 0, 50 and 100% of the amount of P2O5 used in the region for melon) and in the subplots the ten cultivars of melon, for experiment 1 and 8 genotypes, in experiment 2. The following characteristics were evaluated: Productivity, Average fruit weight, number of fruits per plant, foliar content of phosphorus, nutrient demand and agronomic, physiological, recovery and utilization indexes. The results showed that the melon genotypes presented a different behavior in relation to the efficiency of the use of P; The genotypes responded significantly to the increase in phosphorus level in the soil, with increases in the number of fruits per plant, average fruit weight and productivity; Among the evaluated genotypes, the A50 access was efficient and responsive, and could be indicated to increase the efficiency in the use of P through crosses with improved cultivars or lineages; The highest accumulations of NPK were observed in the A50 genotype
Efficiency and nutritional demand of melon cultivars as a function of phosphorus doses
Keywords: Cucumis melo; Nutrição; Indices de eficiência; Cultivares; Cucumis melo; Nutrition; Efficiency ratios; Cultivars; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA